Framework, Development, and Evaluation of Geography Literacy-Based Learning Model for Enhancing Students' Life Skills in Indonesian Senior High School - Muhammad Arif Yudia Mulyadi; Enok Maryani; Mamat Ruhimat; Iwan Setiawan (JAMBURA GEO EDUCATION JOURNAL, 2025)
This study developed a geography instruction framework based on geographic literacy to enhance high school students' life skills. This study was motivated by the limited relevance of conventional geography education to students’ real-life needs, particularly for those who do not pursue higher education. The model was designed using the ASSURE framework, which includes learner analysis, objective formulation, selection and utilization of media, student engagement, systematic evaluation, and revision. The participants consisted of 37 11th-grade students from SMA Negeri 7 Tasikmalaya.. Data were collected using questionnaires constructed based on indicators of geographic literacy and essential life skills questionnaires. The results from the limited trial indicated significant improvements in both hard skills (spatial data analysis and decision-making) and soft skills (communication and collaboration). The model systematically integrates geographic content, geospatial skills, and spatial perspectives into contextual and cooperative learning activities. These findings demonstrate that geographic literacy can serve as an effective pedagogical approach to equip students with essential 21st-century life skills. The model offers practical guidance for geography teachers in designing learning experiences that are more relevant, applicable, and meaningful.